Analisis tindak tutur lagu deen assalam karya sulaiman al mughni: lokusi, ilokusi dan perlokusi - Caereny, Fajaricha Aurera (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the form of speech contained in the lyrics of the song “Deen As-Salam” by classifying it into three forms of action, namely locution, illocution, and perlocution. This research uses descriptive qualitative approach. The data was collected through listening, listening and recording methods. Which is then analyzed interactively through the process of data reduction, classification, data presentation and conclusion. The results showed that each lyric contains the meaning of speech acts that contain in the type of illocutionary acts of directive, representative, expressive, and declarative forms. The most dominant type is directive illocutionary speech acts. This song reveals da'wah messages, tolerance values, and social expressions that are unique to continue to be studied. The messages in the lyrics not only convey the teachings of Islam as a religion of love and peace, but also encourage people to live out the values ​​of tolerance, mutual respect, and maintaining peace in social life. The dominant illocutionary acts are directive and assertive, reinforcing the song's function as a medium for preaching and social expression, emphasizing that art can be a means of prophetic expression.